As possibilidades do Podcast como ferramenta midiática na educação - Franco, Carolina Machado dos Santos de Sousa (2008)
The proposal of this study is to analyze the possibilities of use of podcast in the education. For this, a qualitative research was made in order to search to understand the phenomenon in depth. An analysis of the interactive medias was become fullfilled and not interactive gifts in web 2,0, of which podcast was detached. A study of this technology was effected, placing in quarrel the common sense of being podcast a radio saw Internet; they had been identified, also, its social uses. The study on the state of the art of podcast it allowed the analysis to interdisciplinar of its possibilities in the field of the education. Moreover, a bibliographical research was made and minute research saw Internet, evidencing itself little amount of relative material to the subject. The work evidenced that the use of podcast in the education presents, between some advantages, the conditions of portabilidade and flexibility of use, so important in a society in net. Its inclusion in the schools, in the Brazilian case, confrots with the resistance of some institutions and professionals of the area.